Total energy - Diamant, R. M. E. (Rudolph Maximilian Eugen) 1925- (International series of monographs in heating, ventilation and refrigeration, v. 6, 1970)
Total Energy discusses the process of generating power where it is wanted and to use the waste heat for useful purposes. The book is comprised of 12 chapters that provide a comprehensive discussion of the various aspects of total energy. The text first introduces the concept of total energy, and then proceeds to detailing the principal prime movers used in total energy production. The next chapters cover steam turbines and governors systems for industrial steam turbo-alternators. Next, the book talks about open- and closed-cycle gas turbines. The next three chapters tackle fuel cell, refrigeration and district heating. Chapter 11 examines the existing total energy schemes in North America, while Chapter 12 presents an economic assessment of total energy. The book will be of great interest to researchers and professionals in the energy industry.--Provided by publisher.